2002
DOI: 10.1002/jhet.5570390618
|View full text |Cite
|
Sign up to set email alerts
|

New optically active pyrazoles: Syntheses and the structural characterization of menthopyrazole analogues

Abstract: New chiral pyrazoles, (4R, 7R)-4-methyl-7-isopropyl-3-phenyl-(3-phenyli s omenthopyrazole; c i s -1) , (4R,7S)-4-methyl-7-isopropyl-(l-menthopyrazole; trans-2), (4R,7R)-4-isopropyl-7-methyl-(isocarvomenthopyrazole, c i s-3) and (4R, 7S) -4 -i s o p r o p y l -7 -m e t h y l -4 , 5 , 6 , 7 -t e t r a h y d r o -1H-indazole (carvomenthopyrazole, trans-3) were prepared. The diastereomeric pairs of these 1-3 were structurally characterized by NMR spectroscopy. The subtle differences of structures of 1-3 should ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Formylation of menthone, under now standard alkoxide/formate ester conditions, was originally reported by Claisen, and was also initially examined in the first synthesis of (−)-cubebol by Yoshikoshi, but the approach was abandoned due to the formation of “an inseparable mixture of epimers” . Subsequently, Tolman noted the generation of a 7:93 epimeric mixture during formylation of menthone using NaOMe/HCO 2 Et and, in a key study, Kashima and co-workers found an identical ratio to Tolman with the (currently undesired) cis-isomer predominating, when starting with menthone (or isomenthone) and using NaH/HCO 2 Et . However, Kashima also observed that the use of LDA (−78 °C) followed by HCO 2 Et led to a 75:25 mixture in favor of the trans isomer.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Formylation of menthone, under now standard alkoxide/formate ester conditions, was originally reported by Claisen, and was also initially examined in the first synthesis of (−)-cubebol by Yoshikoshi, but the approach was abandoned due to the formation of “an inseparable mixture of epimers” . Subsequently, Tolman noted the generation of a 7:93 epimeric mixture during formylation of menthone using NaOMe/HCO 2 Et and, in a key study, Kashima and co-workers found an identical ratio to Tolman with the (currently undesired) cis-isomer predominating, when starting with menthone (or isomenthone) and using NaH/HCO 2 Et . However, Kashima also observed that the use of LDA (−78 °C) followed by HCO 2 Et led to a 75:25 mixture in favor of the trans isomer.…”
Section: Resultsmentioning
confidence: 99%
“…5b Subsequently, Tolman 19 noted the generation of a 7:93 epimeric mixture during formylation of menthone using NaOMe/ HCO 2 Et and, in a key study, Kashima and co-workers found an identical ratio to Tolman with the (currently undesired) cisisomer predominating, when starting with menthone (or isomenthone) and using NaH/HCO 2 Et. 20 However, Kashima also observed that the use of LDA (-78 °C) followed by HCO 2 Et led to a 75:25 mixture in favor of the trans isomer. The latter result could be improved in our hands to give hydroxymethylenementhone (12) (55%, S:R = 98:2 at C-6, Scheme 3) by using HCO 2 CH 2 CF 3 , which was introduced by Zayia for "kinetic formylation".…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations